Correlation of Social Media Use with Adolescent Body Image - Wu, Jiayu (Transactions on Social Science, Education and Humanities Research, 2024)
The use of social media (SM) is a topic that has been widely discussed. As adolescents are at a special period in their lives, it is worth exploring the influence of SM on their body image (BI) cognition. This paper synthesizes recent studies on the association between adolescent social media use (SMU) and body image and examines the relationship between adolescent body image cognition and related behavior changes and social media use. Adolescent social media use was positively correlated with unrealistic body management goal setting and there are gender differences. Whether gaining or losing weight, males want a higher muscle mass. While female is more concerned about weight loss in body management. For behavioral change, greater social media use is associated with more frequent use of body management medications. Increased use of social media is detrimental to weight loss. This article highlights the significant impact of social media on adolescent body images. This paper will also point out some future research directions by comprehensively reviewing the relevant research in recent years.